Red Currant (Ribes rubrum L.) Fruit Waste Extract and Juice as Potential Spasmolytic Agents - Maja Cvetković; Bojana Miladinović; Suzana Branković; Milica Randjelović; Slavoljub Živanović; Nemanja Kitić; Milica Milutinović; Miloš Jovanović; Dušica Stojanović; Haris Nikšić; Katarina Šavikin; Dušanka Kitić (Plants)
Red currant (Ribes rubrum L.) berries are rich in bioactive compounds and exhibit nutritive and protective features. This research examined the content of secondary metabolites of the red currant variety Redpoll lyophilized juice and waste extract and their antioxidative and spasmolytic effects. The flavonol and anthocyanin contents of the samples were determined using high-performance liquid chromatography. The antispasmodic effects were assessed in in vitro conditions, and the potential impact of the samples and possible action mechanisms were revealed. The results showed the prevalence of cyanidin-3-O-glucoside as the dominant anthocyanin with higher content in the juice sample. Quercetin content, as the prevalent flavonol, was higher in the waste sample. The berry juice showed a greater ability for scavenging free radicals, whereas the waste better inhibited lipid peroxidation. The juice was a superior antispasmodic agent for spontaneous, KCl-, CaCl2-, BaCl2-, histamine-, and acetylcholine-induced ileal contractions. This first evaluation of the red currant variety Redpoll lyophilized juice and waste extract indicated the beneficial effects of juice as an antioxidant and spasmolytic agent. Therefore, this red currant juice sample could be designated for the prevention or treatment of gastrointestinal disorders.